Desempenho do irrigâmetro no manejo da água de irrigação na cultura do feijoeiro - Tagliaferre, Cristiano; de Oliveira, Rubens Alves; de Oliveira, Ednaldo Miranda; Batista Baptestini, Julio Cesar; Santos, Lucas da Costa [UNESP] (Univ Fed Rural Semi-arido-ufersa, 2010)
In this work, the aim was to evaluate the performance of Irrigameter in the management of the irrigation water, led in the culture of the bean plant, comparatively to the use of the methods standard of stove, tensiometers, Bouyoucos, automatic meteorological station and pan Class A. Irrigameter was adjusted to the soil characteristics, culture of the bean and irrigation equipment to confection the management ruler. For direct estimation of the evapotranspiration of the culture of the bean plant in your development stadiums, Irrigameter operated inside with heights of the levels of water of the evaporatorio same to 2, 3 and 5 cm, corresponding to the stadiums of initial development, vegetative development and flowering, respectively. The humidity obtained by the standard method of stove it was adopted as reference in the comparisons of the irrigation depth. Irrigameter can be used in the management of the irrigation to determine the consumption of water directly for a culture, in any development stadium; the methods that estimate the evapotranspiration of the culture overestimated the irrigation depth recommended by the standard method of stove, happening behavior contrary with the ones that determines the current humidity of the soil.

Neste trabalho teve-se por objetivo avaliar o desempenho do Irrigâmetro no manejo da água de irrigação, conduzido na cultura do feijoeiro, comparativamente ao uso dos métodos padrão de estufa, tensiômetro, Bouyoucos, estação meteorológica automática e tanque Classe A. O Irrigâmetro foi ajustado às características de solo, cultura do feijão e equipamento de irrigação para confeccionar as réguas de manejo. Para estimativa direta da evapotranspiração da cultura do feijoeiro nos seus estádios de desenvolvimento, o Irrigâmetro operou com alturas dos níveis de água dentro do evaporatório iguais a 2, 3 e 5 cm, correspondendo aos estádios de desenvolvimento inicial, desenvolvimento vegetativo e floração, respectivamente. A umidade obtida pelo método padrão de estufa foi adotada como referência nas comparações das lâminas de irrigação. O Irrigâmetro pode ser usado no manejo da irrigação para determinar diretamente o consumo de água por uma cultura, em qualquer estádio de desenvolvimento; os métodos que estimam a evapotranspiração da cultura superestimaram a lâmina de irrigação recomendada pelo método padrão de estufa, ocorrendo comportamento contrário com os que determinam a umidade atual do solo.
Irrigameter performance in irrigation water management in common bean crop
Keywords: Irrigation depth; Crop evapotranspiration; Evaporation